Corrosion in Advanced Nuclear Reactors. (June 2021) - Was, Gary S.; Allen, Todd R.
Abstract : Commercial nuclear power plants in the United States are light water reactors (LWRs) that use water as a coolant, with temperatures ranging between 280°C and 320°C. Water purity is tightly controlled; nevertheless, the high temperatures expose components in the water circuit to degradation by corrosion by many different types of environmental attack. Uniform corrosion occurs across the entire surface of a material and is prevalent in engineering systems to some extent. Site-specific corrosion processes, such as crevice corrosion, intergranular attack, or galvanic corrosion, are common in complex engineering systems that consist of multiple materials joined by welds or other solid state joining processes. Even within a single component, if second phase strengthening is used or if surface defects are present, localized corrosion can occur.